Unmet needs in the international neuroendocrine tumor (NET) community: Assessment of major gaps from the perspective of patients, patient advocates and NET health care professionals. Issue 5 (25th October 2019) - Leyden, Simone; Kolarova, Teodora; Bouvier, Catherine; Caplin, Martyn; Conroy, Siobhan; Davies, Phillipa; Dureja, Sugandha; Falconi, Massimo; Ferolla, Piero; Fisher, George; Goldstein, Grace; Hicks, Rodney J.; et al.
Abstract : Due to the increasing incidence and prevalence of neuroendocrine tumors (NETs), there is a need to assess any gaps in awareness and care. A survey was undertaken in 2017 to identify perceived unmet needs from the perspectives of patients/families, patient advocates and health care professionals (HCPs). The survey consisted of 33–37 questions (depending on type of respondent) across four areas: information, care, treatments and research. In total, 443 participants from 26 countries responded: 338 patients/families, 35 advocates and 70 HCPs. Perceived unmet needs regarding provision of information at diagnosis differed between groups. While 59% of HCPs believed they provided sufficient information, informational needs were mostly/fully met for only 30% of patients and 18% of advocates. Additionally, 91% of patients and 97% of advocates felt that patients had to search for information themselves. Availability of Gallium‐68‐Dotatate PET/CT scan was limited for the majority of patients (patients: 73%; advocates: 85%; HCP: 86%), as was access to treatments, particularly peptide receptor radionuclide therapy (patients: 42%; advocates: 95%; HCPs: 77%). All groups felt that standards of care, including psychological needs and diagnosis of mental health, were not fully met. Although about two‐thirds of patients were managed by a multidisciplinary team, 14% of patients reportedly did not have enough contact. All groups supported more patient involvement in research; patients and advocates prioritized improvement in diagnosis and HCPs focused on clinical trials. This survey revealed significant unmet needs but differing perceptions regarding these among the groups. There is a need for investigation and collaboration to improve standards of care for NET patients. Abstract : What's new? Even though the incidence of neuroendocrine tumors (NETs) has been rising worldwide, the current management of patients varies considerably, potentially leaving many with suboptimal care. An international survey was carried out in 2017 to investigate unmet needs in the NET patient community. The survey revealed that patients perceive numerous unmet needs in key areas including provision of information, diagnostics and treatment access, care standards, and research involvement. While healthcare professionals were aware of these gaps, they generally underestimated their magnitude. Patients and healthcare professionals need to work together to improve the lives and prospects of the increasing numbers of patients.